2009
DOI: 10.1159/000207357
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption, Allergic Sensitisation and Allergic Diseases in Adults

Abstract: Background: Previous studies have suggested that fish intake plays a protective role in the development of allergic diseases because of its high content of n-3 very long chain polyunsaturated fatty acid (VLC-PUFA). However, it is not clear whether fish intake also has a beneficial effect in adulthood, when allergic diseases are thought to be predominantly manifested. Methods: Data from 388 adults from German study centres within the European Community Respiratory Health Study II were analysed. These subjects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…One report indicates that there could be a gender-related difference in the metabolism of PUFA, whereas another study reported that individuals with fish allergies could safely tolerate fish oil supplements. 53,54 Black currant seed oil has been used safely in a number of human clinical studies, and no reports of rash associated with this oil appear in the Food and Drug Administration MedWatch Adverse Effects Reporting System Database. 23,55,56 In our study, 1 of 19 supplement-treated patients reported a rash during the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“…One report indicates that there could be a gender-related difference in the metabolism of PUFA, whereas another study reported that individuals with fish allergies could safely tolerate fish oil supplements. 53,54 Black currant seed oil has been used safely in a number of human clinical studies, and no reports of rash associated with this oil appear in the Food and Drug Administration MedWatch Adverse Effects Reporting System Database. 23,55,56 In our study, 1 of 19 supplement-treated patients reported a rash during the course of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Adult females with a high fish and DHA intake showed a lower rate of allergic sensitisation None Schnappinger et al (66) 121 The EPA-predominant supplement raised DHA only in the young, and the DHA-predominant supplement raised EPA more in the young None Fortier et al (71) 302 cognitively healthy elderly participants (. 65 y) (72,73,76) 1864 subjects (809 men and 1055 women 8-y follow-up survey of the SU.VI.MAX Study (1994 -2002) Assessment of fish and seafood, and n-3 LC-PUFAs intake by means of six 24-h recalls Fatty fish or n-3 LC-PUFAs consumption higher than 0•10 % of energy intake had lesser risk of depressive episode and of recurrent depressive episodes, but not of single depressive episode.…”
Section: S29mentioning
confidence: 99%
“…Two surveys in adults found associations between fish consumption and a lower risk of allergy/asthma. In the study by Schnappinger et al . (2009), IgE levels and lung function were measured in 388 adults.…”
Section: Associations With Health and Wellnessmentioning
confidence: 98%